ELASTIC-PLASTIC ANALYSIS FOR THERMOPLASTIC COMPOSITE PLANE CURVED BEAMS BY BENDING MOMENT - LIU MingWei; GAO YiHang; ZHANG DaPeng; WANG ZhiXiang; LEI YongJun (Jixie qiangdu)
Thermoplastic composites have excellent comprehensive mechanical properties and widely applied prospects. A static model was established and elastic-plastic characteristics were analyzed for a plane curved beam,which was made of thermoplastic composites and subjected to bending. Based on the single parameter plastic modal,the associated flow rules and the linear strain hardening law,the governing equations of curved beams were derived according to the basic equations of plane stress problem in polar coordinates. The analytical solutions of stress and displacement were then obtained. The influence of geometrical size on stress distribution at the cross-section of the curved beam was analyzed. Also,the failure mode of the curved beam was judged in virtue of the Hashin failure criterion. The results demonstrate the efficiency of the proposed model for elastic-plastic characteristics analysis of thermoplastic composite curved beams subjected to bending. And the failure mode of curved beams is associated with the radius-thickness ratio.